Detection of the Non-SMC Condensin I Complex Subunit G Gene Polymorphism (NCAPG c.1326 T>G) in Different Breeds of Cattle - Anna Trakovická; Michal Gábor; Martina Miluchová; Tomáš Minarovič; Danka Štastná (Scientific Papers Animal Science and Biotechnologies, 2023)
The non-synonymous mutation c.1326 T>G in the non-SMC condesin I complex subunit G (NCAPG) gene is asociate with the prenatal growth and carcass weight or growth-associated traits in cattle. The aim of this study was to analyse the population of 50 sires of four breeds (Holstein – 2 bulls, Pinzgau – 3 bulls, Charolais – 3 bulls, Simmental – 42 bulls) for SNP polymorphism causing an exchange from isoleucine to methionine at position 422 of the amino acid chain. Bovine genomic DNA was isolated from sperm by commercial kit. The SNP c.1326 T>G was detected by PCR-RFLP method with restriction endonuclease Tsp509I. The wild allele T was detected by two restriction fragments 66 bp and 63 bp and the mutant allele G with 129 bp fragment. In the samples of Pinzgau sires, Charolais sires and Simmental sires were detected homozygous genotypes GG (0.3333; 0.3333 and 0.7143) and heterozygous genotype GT (0.6667; 0.6667 and 0.2857). In the sample of Holstein sires were detected homozygous genotype GG (0.5) and homozygous genotype TT (0.5).